MENGGALI TEORI KOMUNIKASI JÜRGEN HABERMAS TERKAIT PARTISIPASI MASYARAKAT MELALUI RUANG PUBLIK DIGITAL: STUDI KASUS APLIKASI X - Rossalia Amanda; Berliandini Utami; Tobat Lumban Gaol (SOSFILKOM : Jurnal Sosial, Filsafat dan Komunikasi, 2025)
This article explores the dynamics of the digital public sphere through the theoretical lens of Jürgen Habermas' communication theory, focusing specifically on how the social media platform X (formerly Twitter) serves as a site of civic participation in contemporary public discourse. Employing a qualitative approach through comprehensive library research, this study engages critically with literature on communicative action, the transformation of the public sphere, and digital communication behavior, particularly in the Indonesian context. The findings reveal that although platform X provides technical infrastructure for rapid and widespread opinion exchange, public discussions on the platform are often trapped in polarization, identity-based digital tribalism, and emotionally charged interactions that hinder the realization of communicative rationality as envisioned by Habermas. The dominance of engagement-driven algorithms, rampant misinformation, and the general lack of digital literacy further exacerbate this condition, rendering digital platforms more as arenas of ideological conflict and disinformation than spaces of meaningful deliberation. Consequently, this article recommends strengthening digital literacy grounded in ethical discourse principles, advocating for algorithmic transparency and fairness, and encouraging the proactive involvement of educational institutions and state actors in shaping a healthier, more reflective, and inclusive digital public sphere in alignment with Habermas' ideals of deliberative democracy.